The Reciprocal Relationship Between Parental eHealth Literacy Mediation and Adolescents' eHealth Literacy: Three-Wave Longitudinal Study - Tercova, Natalie; Muzik, Michal; Dedkova, Lenka; Smahel, David (Journal of medical Internet research, 2025)
BACKGROUND: The online environment provides adolescents with vast amounts of health-related information; however, navigating this effectively requires high levels of eHealth literacy to avoid misinformation and harmful content. Parental guidance is often considered a crucial factor in shaping adolescents' online health behaviors; however, there is limited longitudinal research examining how parental eHealth literacy mediation influences adolescents' development of eHealth literacy over time. OBJECTIVE: This study aims to examine the reciprocal relationship between parental eHealth literacy mediation and adolescents' eHealth literacy. It also investigates whether parental education moderates this relationship, specifically exploring whether higher levels of parental education enhance the effectiveness of eHealth literacy mediation in improving adolescents' eHealth literacy. METHODS: A 3-wave longitudinal study was conducted, collecting data from 2500 adolescent-parent pairs. A random intercept cross-lagged panel model was applied to assess the reciprocal effects between parental eHealth literacy mediation and adolescents' eHealth literacy across the 3 waves. Parental education was included in the model as a potential moderating variable to examine whether it influences the strength of the relationship between parental eHealth literacy mediation and adolescents' eHealth literacy. RESULTS: The findings revealed no significant within-person effects, indicating that changes in parental eHealth literacy mediation over time did not lead to corresponding changes in adolescents' eHealth literacy (T1→T2 β=-.03, P=.65; T2→T3 β=.01, P=.84), and vice versa (T1→T2 β=.02, P=.71; T2→T3 β=-.07, P=.19). Furthermore, the data did not support a moderating effect of parental education, suggesting that higher educational attainment does not enhance the impact of parental eHealth literacy mediation. However, a significant between-person association was observed: adolescents with higher levels of eHealth literacy tend to have parents who engage more frequently in eHealth literacy mediation (r=0.30, P<.001). CONCLUSIONS: This study contributes to the understanding of parental involvement in shaping adolescents' eHealth literacy. Contrary to expectations, parental eHealth literacy mediation does not appear to have a significant longitudinal impact on the development of adolescents' eHealth literacy, nor does higher parental education strengthen this relationship. These findings suggest that additional factors beyond parental mediation and education may play a critical role in supporting adolescents' ability to navigate online health information effectively.
Keywords: Adolescent; Telemedicine; adolescents; zdravotní gramotnost; mužské pohlaví; longitudinální studie; vztahy mezi rodiči a dětmi; Humans; longitudinal research; telemedicína; lidé; eHealth literacy; Parent-Child Relations; eHealth mediation; mladiství; Longitudinal Studies; Female; health information; Health Literacy; rodiče; ženské pohlaví; Male; Parents; parental mediation